Electromagnetic fields act via activation of voltage‐gated calcium channels to produce beneficial or adverse effects - Pall, Martin L. (Journal of cellular and molecular medicine, 2013)
The direct targets of extremely low and microwave frequency range electromagnetic fields (EMFs) in producing non‐thermal effects have not been clearly established. However, studies in the literature, reviewed here, provide substantial support for such direct targets. Twenty‐three studies have shown that voltage‐gated calcium channels (VGCCs) produce these and other EMF effects, such that the L‐type or other VGCC blockers block or greatly lower diverse EMF effects. Furthermore, the voltage‐gated properties of these channels may provide biophysically plausible mechanisms for EMF biological effects. Downstream responses of such EMF exposures may be mediated through Ca2+/calmodulin stimulation of nitric oxide synthesis. Potentially, physiological/therapeutic responses may be largely as a result of nitric oxide‐cGMP‐protein kinase G pathway stimulation. A well‐studied example of such an apparent therapeutic response, EMF stimulation of bone growth, appears to work along this pathway. However, pathophysiological responses to EMFs may be as a result of nitric oxide‐peroxynitrite‐oxidative stress pathway of action. A single such well‐documented example, EMF induction of DNA single‐strand breaks in cells, as measured by alkaline comet assays, is reviewed here. Such single‐strand breaks are known to be produced through the action of this pathway. Data on the mechanism of EMF induction of such breaks are limited; what data are available support this proposed mechanism. Other Ca2+‐mediated regulatory changes, independent of nitric oxide, may also have roles. This article reviews, then, a substantially supported set of targets, VGCCs, whose stimulation produces non‐thermal EMF responses by humans/higher animals with downstream effects involving Ca2+/calmodulin‐dependent nitric oxide increases, which may explain therapeutic and pathophysiological effects.